Non-violence in philosophical and religious ethics - Christians, Clifford G. (Javnost (Ljubljana), 2007)
Along with human dignity and truth telling, non-violence is an ethical principle entailed by the sacredness of life. My purpose in this paper is to examine non-violence from the perspective of religion. Hans Kung argues that all religions agree on the common ethical principle that war and violence are immoral. The ethical system of all major world religions is centered on the non-violence of the golden rule - "do to others as you would have them do to you." Martin Luther King's philosophical perspective on non-violence was deeply religious in character. Religious perspectives appear to support and enrich non-violence as a universal principle of ethics. But the issue is inclusiveness. Are religious perspectives only relevant for adherents? The Dali Lama presents a moral system based on universal human ethics rather than on religious principles. That convergence Michael Traber represented also. An approach that sees religious perspectives in positive terms, as enabling a commitment to non-violence, must confront the dilemma that religious beliefs generate conflict more than they promote tolerance. This conundrum is confronted through the principle-practice distinction. An ethics of non-violence that is credible philosophically and religiously gives us leverage for action in the spirit of Michael Traber.
Keywords: vera; religija; religion; philosophy; filozofija; ethics; etika; nenasilje